1988
DOI: 10.1007/bf01535781
|View full text |Cite
|
Sign up to set email alerts
|

24-hour study of intragastric acidity in duodenal ulcer patients and normal subjects using continuous intraluminal pH-metry

Abstract: The circadian pattern of intragastric acidity was assessed in 19 healthy subjects and 37 patients with active, endoscopically proven duodenal ulcer using 24-hr continuous intraluminal pH-metry. The median pH 24-hr profiles showed that ulcer patients had lower postprandial pH elevations and a smaller decline in acidity during the early morning hours when compared with controls. The after-lunch and -dinner area under the curve and maximum pH values were significantly higher in controls compared to ulcer patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 15 publications
3
18
0
Order By: Relevance
“…Consequently it has been reported that N is the least reproducible reflux parameter, and the most reproducible is % [12,13]. Gastric acid secretion is known to be greatest in the early part of the night as a continuation of evening meal stimulated output, decreasing to near-normal subject basal levels by halfway through the night [14][15][16]. This may explain the predominance of gastroesophageal acid reflux in the first half of the night.…”
Section: Discussionmentioning
confidence: 94%
“…Consequently it has been reported that N is the least reproducible reflux parameter, and the most reproducible is % [12,13]. Gastric acid secretion is known to be greatest in the early part of the night as a continuation of evening meal stimulated output, decreasing to near-normal subject basal levels by halfway through the night [14][15][16]. This may explain the predominance of gastroesophageal acid reflux in the first half of the night.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast to the slight alkalinity of the fasting python's stomach, mammals maintain a highly acidic environment (pH 1.1-3) within their stomachs between bouts of digestion (Youngberg et al, 1985;Evans et al, 1988;Cilluffo et al, 1990;Viani et al, 2002). Whereas pythons experience a dramatic postprandial decrease in gastric pH, the luminal pH of mammal stomachs increases rapidly after feeding to range between 3 and 6, presumably as the ingested meal buffers the gastric acid (Savarino et al, 1988;McLauchlan et al, 1989;Cilluffo et al, 1990). Within a few hours after feeding, intragastric pH of mammals drops as acid production, which has increased 20-fold, overwhelms the buffering capacity of the food, which is then being passed through the pyloric sphincter into the small intestine (Fordtran and Walsh, 1973).…”
Section: Gastric Phmentioning
confidence: 99%
“…A previous study concluded that omeprazole produces profound gastric anacidity or achlorhydria over 24 h [6, 7]. However, the gastric aspiration techniques used in this study pooled secretions collected over the previous hour, thereby obscuring the temporal pH variations observed during ambulatory, 24-hour, single-electrode recordings of gastric pH [8, 9, 10]as well as the regional, intragastric variations detected in multi-electrode studies [10, 11]. Such regional differences in the pH of gastric contents might also explain, in part, the marked variations in response observed with omeprazole therapy in individual patients with gastro-esophageal reflux disease since acidic material could reflux into the esophagus from localized pockets low pH, thereby producing esophageal mucosal damage.…”
Section: Introductionmentioning
confidence: 88%